SARS-CoV-2 infection in a hippopotamus, Hanoi, Vietnam - Vuong Nghia Bui; Tung Duy Dao; Long Hoang Tran; Thanh Thi Vu; Trang Huyen Nguyen; Giang Hoang Nguyen; Kien Viet Dung Tran; Huyen Xuan Nguyen; Anh Ngoc Bui; Unger, Fred; Hung Nguyen-Viet; Hu Suk Lee (Centers for Disease Control and Prevention, 2023)
While investigating the death of a hippopotamus at a zoo in Hanoi, Vietnam, we isolated SARS-CoV-2 and sequenced the RNA-dependent RNA polymerase gene from different organs. Phylogenetic analysis showed that the SARS-CoV-2 strain was closely related to 3 human SARS-CoV-2 strains in Vietnam.